Trách nhiệm xã hội doanh nghiệp: Các xu hướng nghiên cứu - Hồ Viết , Tiến; Hồ Thị Vân , Anh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2019)
The research of corporate social responsibility seems to be started by research of Caroll (1979) on the three-dimensional conceptual model of corporate performance - economic, social and environmental. It has only been strongly developed since the years of 2010 in different levels of approaches and related to different aspects of management, such as strategic management, human resource management, marketing, finance, accounting, environmental management… This article aims to establish a review of corporate social responsibility researches, background theories, current topics on three levels of institutional, organizational and individual, methods applied and data used in research and topics of corporate social responsibility in the years to come.
Keywords: Corporate Social Responsibility; Corporate Social Performance; Corporate Financial Performance; Institutional Approach; Organizational Approach; Individual Approach